Waiting for the Sybil (Vergilius: Aeneis 6,14–41) - Darab, Ágnes (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The sixth book of Virgil’s Aeneid stands out from the text because it is the crystallization of the structural and allusive procedures that organize the text. The narrative of the founding myth of the Temple of Apollo in Cumae and the description of the reliefs decorating the temple’s gate, with the figure of the mythical architect-inventor-sculptor Daedalus in the center (6,14–41), were placed at a highlighted position within the key sixth book: at the beginning. Aeneid philology interprets the temple scene of the sixth book mostly from the point of view of ekphrasis, more precisely in connection with the other ekphrases in the Aeneid. In my paper, I will not concentrate on the interpretation of Daedalus’ reliefs, but on the entirety of the Cumae scene. Specifically from the perspective of the roles, I shall examine the layers of meaning that can be formed in the textual space of Aeneid around Aeneas’ scrutiny of the image during the time of waiting and around the narrator’s description of the image.